2019
DOI: 10.1039/c9ta06347a
|View full text |Cite
|
Sign up to set email alerts
|

Defective and ultrathin NiFe LDH nanosheets decorated on V-doped Ni3S2 nanorod arrays: a 3D core–shell electrocatalyst for efficient water oxidation

Abstract: Defective and ultrathin NiFe LDH nanosheets decorated on V-doped Ni3S2 nanorod arrays were fabricated as 3D core–shell electrocatalysts for OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(68 citation statements)
references
References 37 publications
3
65
0
Order By: Relevance
“…The fabrication of heterojunctions in catalyst would be a new strategy to promote their catalytic activities by purposefully regulating the electronic structure of active sites. For the past few years, many other 3D hierarchical nanoarrays on conductive 3D networks, such as CoFe LDH/Co 0.85 Se/carbon cloth, NiFe LDH@NiFe-Bi/carbon cloth, and NiSe/NiFe LDH/Ni foam, have been reported as high-performance OER catalysts [139][140][141][142][143][144].…”
Section: Construction Of 3d Freestanding Electrodes Based On Ldhsmentioning
confidence: 99%
“…The fabrication of heterojunctions in catalyst would be a new strategy to promote their catalytic activities by purposefully regulating the electronic structure of active sites. For the past few years, many other 3D hierarchical nanoarrays on conductive 3D networks, such as CoFe LDH/Co 0.85 Se/carbon cloth, NiFe LDH@NiFe-Bi/carbon cloth, and NiSe/NiFe LDH/Ni foam, have been reported as high-performance OER catalysts [139][140][141][142][143][144].…”
Section: Construction Of 3d Freestanding Electrodes Based On Ldhsmentioning
confidence: 99%
“…[9] Zhou et al investigated the OER catalytic capability of 1D V-doped Ni 3 S 2 nanorod arrays with a layer of 2D NiFe LDH nanosheets in alkaline electrolyte, and evaluated their activity for overall water splitting. [27] In addition, Wang et al and Xie et al reported the synthesis of Cu-derived nanowire arrays acting as the 1D core and coated with 2D ZnCo layered double hydroxide or 1D CoCO 3 (OH) 2 •nH 2 O nanowires for highly-efficient OER electrocatalysis. [24,25] Overall, these studies demonstrate the superiority of 3D hierarchical nanostructures as applied to water oxidation.…”
mentioning
confidence: 99%
“…To further reveal the origins of the outstanding OER activity of Ni x B/B 4 C/B−C PR /NF−B5P1, the double layer capacitance ( C dl ) is concluded from the cyclic voltammetry curve (CV) (0.1–0.2 V vs. Hg/HgO) with the non‐faradaic region (Figure S7a–e). The Ni x B/B 4 C/B−C PR /NF−B5P1 exhibits the largest C dl (320.3 mF cm −2 ) among these as‐prepared samples (Figure S7f), implying that a larger electrochemical active surface area is attributed to high space utilization, which benefits the diffusion and adsorption of electrolytes and gaseous products [31] . The current density is normalized by the electrochemical active surface area (ECSA), and the Ni x B/B 4 C/B−C PR /NF−B5P1 catalyst still exhibits best OER activity compared with the others (Figure S8).…”
Section: Resultsmentioning
confidence: 99%